Microstrip Tunable Bandpass Filter with the Colinear Resonators - Z. P. Wang; P. S. Hall; J. Kelly; P. Gardner (International Journal of Antennas and Propagation)
This paper presents the lumped element circuit and transmission line equivalent circuit for a varactor-tuned bandpass filter. The filter consists of transmission lines, fixed capacitors, and a varactor diode. The colinear resonant sections, in this filter, are not configured in parallel, as they are in a conventional combline filter. For this reason the overall area of the filter is reduced. The passband of the filter can be tuned from 0.69 GHz to 1.20 GHz by varying the capacitance of the varactor diode. The insertion loss of this filter changes from 1.2 dB to 2.1 dB across this bandwidth.